Bismuth erbium-doped fiber based multi-wavelength laser assisted by four-wave mixing process - Harun, Sulaiman Wadi; Shahi, Sharifeh; Ahmad, Harith (Institute of Electronics, Information and Communication Engineers (IEICE), 2009)
We demonstrate for the first time a multi-wavelength laser based on a bismuth-based erbium-doped fiber (Bi-EDF) assisted by a four-wave mixing (FWM) process. Using a simple linear cavity resonator scheme containing a 49 cm long highly nonlinear Bi-EDF, we obtained about 8 lines of optical comb with a line spacing of approximately 0.52 nm at the maximum 1480 nm pump power of 160 mW.